OPINI GOING CONCERN: PENGARUH LEVERAGE, OPINI AUDIT SEBELUMNYA, PERTUMBUHAN DAN KUALITAS AUDIT - Anam, Hairul (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of leverage, previous year's audit opinion, entity growth and audit quality on going concern audit opinion acceptance. The research sample was 184. The analytical method used is logistic regression analysis. Based on the results of the analysis, it can be concluded that leverage has no effect on going concern audit opinion, previous year's audit opinion does not affect going concern audit opinion, entity growth affects going concern audit opinion, and audit quality does not affect going concern audit opinion.